PENGARUH PRESTASI KERJA DAN KOMPETENSI TERHADAP PROMOSI JABATAN KARYAWAN PT PERKEBUNAN NUSANTARA V PEKANBARU (Studi pada Kantor Pusat PT Perkebunan Nusantara V Pekanbaru) - Siringoringo, Rohana; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study uses 3 variables, namely job performance, competence, and promotion position. The job performance variable has 4 dimensions, namely skills and abilities, discipline, personality, and responsibility. In the competency variable has 3 dimensions, namely knowledge, work experience, and able to analyze. On variables promotion position has 7 dimensions, namely aspects of honesty, aspects of discipline, aspects of work performance, aspects of loyalty, educational aspects, aspects of leadership, and communicative aspects. This study was conducted on all employee of the Head Office PT Perkebunan Nusantara V Pekanbaru 83 peoples.  Data obtained from questionnaires and then processed then tested using statistical analysis such as validity test, reliability test, simple linear regression, multiple linear regression, determination test (R2), significant individual test (t test), and simultaneous significant test (f test) with using the SPSS program. The results of the study indicate the influence of Job Performance and Competence on Position Promotion. The better job performance and employee competency, the greater the likelihood of being promoted to higher rankings. The results of the calculation of the determination coefficient (R2) obtained the value of R Square of 0.659. The meaning is that the contribution of promotion position variables and competencies to job promotion variable is 65.9%. Keyword : Job Performance, Competence, Promotion Position